The role of physical activities and clinical risk factors on cognitive reserve: Preliminary results on an Argentine population of older adults - Feldberg, Carolina (2020)
Background: Lifestyle plays an important role in the way people age. In recent decades, increasing attention has been paid to the role ofleisure activities. Evidence from different studies, supports the hypothesis that increased physical activity prevents the onset of cognitive decline. Aerobic exercise has been associated with an increase in cognitive functioning and general wellbeing. The aim of the present study is to analyze if there is a difference in the participation in physical activities between patients with MCI and healthy older adults living in CABA, Argentina.Method: This was a retrospective comparative study of 145 MCI patients (n= 82) (M=76, 74 years old; ds=6.8 years) and healthy older adults (n=63) (M=71.51 years (ds=8.92) Instruments: Questionnaire of Social Demographic Data (built ad hoc), Questionnaire of Social Participation and an extensive neuropsychological battery that assed memory, attention, language, executive functions and visuospatial abilities was administered.Results: Results reveal that when comparing the groups, statistically significant differences in favor of the group of healthy older adults were found in their involvement in: swimming (F(145, 1) = 6.11 p < .001), walking (F(145, 1) = 18.01 p < .000),aerobic gymnastics (F(145, 1) = 4.1, p < .05), biking (F(145, 1) = 3.45, p < .05). Conclusions: These results agree with other studies which identified the factors that promote healthy cognitive aging in older adults. Within the framework of cognitive reserve, physical activities like: walking, biking, swimming and gymnastics play a differential and important role in the course of cognitive aging. The present study coincides with other researches, and adds empirical evidence of interest for the clinical and scientific fields of healthy cognitive ageing.